2004
DOI: 10.1124/jpet.104.074450
|View full text |Cite
|
Sign up to set email alerts
|

β-Amyloid-Induced Neurodegeneration and Protection by Structurally Diverse Microtubule-Stabilizing Agents

Abstract: Deposition of ␤-amyloid peptide (A␤) and hyperphosphorylation of the protein are associated with neuronal dysfunction and cell death in Alzheimer's disease. Although the relationship between these two processes is not yet understood, studies have shown that both in vitro and in vivo exposure of neurons to A␤ leads to hyperphosphorylation and neuronal dystrophy. We previously reported that the microtubule-stabilizing drug paclitaxel (Taxol) protects primary neurons against toxicity induced by the A␤ [25][26][27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
78
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 40 publications
(61 reference statements)
7
78
1
1
Order By: Relevance
“…We note that our finding that short exposures to Ab can induce MT stability in neurons challenges the current interpretation that a primary activity of Ab is to cause MT destabilization through tau hyperphosphorylation (Michaelis et al, 1998) Michaelis et al, 2005;Zempel et al, 2010;Zhang et al, 2012). We believe that our data, although surprising, are not in contradiction with the current model but rather suggest an original interpretation that deserves further testing, that is that progressive MT destabilization upon exposure to Ab might be a consequence of the cellular response to counteract a chronic induction in the levels of stable Glu MTs.…”
Section: Discussioncontrasting
confidence: 78%
“…We note that our finding that short exposures to Ab can induce MT stability in neurons challenges the current interpretation that a primary activity of Ab is to cause MT destabilization through tau hyperphosphorylation (Michaelis et al, 1998) Michaelis et al, 2005;Zempel et al, 2010;Zhang et al, 2012). We believe that our data, although surprising, are not in contradiction with the current model but rather suggest an original interpretation that deserves further testing, that is that progressive MT destabilization upon exposure to Ab might be a consequence of the cellular response to counteract a chronic induction in the levels of stable Glu MTs.…”
Section: Discussioncontrasting
confidence: 78%
“…Paclitaxel also blocks Aβ-induced phosphorylation of tau by preventing the cleavage of p35 by calpain (Li et al 2003). Nanomolar concentrations of paclitaxel can protect neurons against various toxic insults and enhance survival by maintaining Ca 2+ homeostasis (Burke et al 1994;Furukawa and Mattson 1995;Furukawa et al 2003;Sponne et al 2003;Michaelis et al 2005) without evidence of toxicity (Trushina et al 2003). Our study demonstrates that tau is not phosphorylated by MTstabilizing/destabilizing drugs at lower doses, but it is phosphorylated at higher doses.…”
Section: Discussionmentioning
confidence: 61%
“…We used Aβ [25][26][27][28][29][30][31][32][33][34][35] at a concentration of 10 μM in the present studies based on earlier results. In previous studies we have shown that at this concentration we see Aβ induced loss of cortical cells by approximately 50% [20]. This level thus enables us to test drug effects that would not be possible if high Aβ concentration were used to destroy all cells.…”
Section: Measurement Of Cell Viabilitymentioning
confidence: 75%